All-Optical Amplitude Multiplexing Through Fiber Parametric Interaction Between Binary Signals - Abbade, Marcelo L. F.; Marconi, Jorge D.; Fagotto, Eric A. M.; Barbosa, Felipe R.; Costa, André L. A.; Fonseca, Iguatemi E.; Moschim, Edson (IntechOpen, 2012)
None